Beyond return : genre and cultural politics in contemporary French fiction - Hollister, Lucas (Contemporary French and francophone cultures., 2019)
In Beyond Return, Lucas Hollister examines the political orientations of fictions which 'return' to forms that have often been considered sub-literary, regressive, outdated or decadent, and suggests new ways of reading contemporary adventure novels, radical noir novels, postmodernist mysteries, war novels and dystopian fictions.